Haloxylon Salicornicum - An Arid Land Shrub : It’s Ecology and Potential - Kaul, Anita (Annals of Arid Zone, 2016)
Haloxylon salicornicum (Moq.) Bunge, a succulent dwarf chenoped shrub, grows naturally in the extreme arid regions of the world. It is an important forage shrub as it remains green and available to the livestock during the lean period (November-March) when the green pasturage is scarce. It is also used as a descaling agent for locomotive boilers as it contains high percentage of oxalic acid. Some new piperidine alkaloids have also been isolated from this shrub. Several aspects of its biology and utilization have also been studied. These findings have been described and discussed in this paper. Gaps in the available information and future line of research have also been indicated.